2022
DOI: 10.22144/ctu.jen.2022.028
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of medicinal plant resources in Lai Son island, Kien Giang province

Abstract: This study was conducted with the aim of assessing the diversity of medicinal plants in Lai Son Island, Kien Giang province, which is a scientific basis for more effectively using, managing, and preserving this medicinal plant resource in this province. In this study, the PRA (Participatory Rural Appraisal), field investigation, morphological comparison, and classification, with the aid of specialized medicinal plant books were used. The results showed a total of 353 species of medicinal plants belonging to 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…), and mountains in An Giang Province, no reports were found in the plains. In the survey of three islands of Kien Giang Province, Nguyen and Nguyen found that the subspecies usually hang on the branches and leaves of mango trees (Laidlaw and Solem, 1961;Sutcharit et al, 2006;Schileyko, 2011;Inkhavilay et al, 2017;Nguyen and Nguyen, 2016). On the contrary, there were no individuals of the snail found in that type of tree but in landscaping plants (Dipterocarpus alatus, Samanea saman, Khaya senegalensis, and Erythrina fusca) in this study.…”
Section: Additional Information Of Amphidromuscontrasting
confidence: 61%
See 3 more Smart Citations
“…), and mountains in An Giang Province, no reports were found in the plains. In the survey of three islands of Kien Giang Province, Nguyen and Nguyen found that the subspecies usually hang on the branches and leaves of mango trees (Laidlaw and Solem, 1961;Sutcharit et al, 2006;Schileyko, 2011;Inkhavilay et al, 2017;Nguyen and Nguyen, 2016). On the contrary, there were no individuals of the snail found in that type of tree but in landscaping plants (Dipterocarpus alatus, Samanea saman, Khaya senegalensis, and Erythrina fusca) in this study.…”
Section: Additional Information Of Amphidromuscontrasting
confidence: 61%
“…Distribution: Vietnam (Kien Giang, An Giang, Ho Chi Minh city, Dong Nai, Phu Yen); Cambodia; Thailand; Laos (Laidlaw and Solem, 1961;Sutcharit et al, 2006;Schileyko, 2011;Inkhavilay et al, 2017;Nguyen and Nguyen, 2016). Prior to this study, several records found A. inversus annamiticus in the Cuu Long River Delta only in mountains and islands of Kien Giang Province (Kien Luong Distr., Ha Tien Distr., and Kien Hai Distr.…”
Section: Additional Information Of Amphidromusmentioning
confidence: 81%
See 2 more Smart Citations
“…Hệ thực vật ở đây ngày càng bị suy thoái, nhiều loài quí hiếm đang có nguy cơ tuyệt chủng, trong khi sự tái sinh của chúng trong môi trường tự nhiên lại rất chậm và khó có khả năng phục hồi. Mặc dù đảo Lại Sơn là một đảo khá lớn, có nhiều người dân sinh sống và du lịch rất phát triển, nhưng mới chỉ có công trình nghiên cứu về tài nguyên cây làm thuốc được công bố (Quan & Phuc, 2022), còn nhiều loài thực vật có các giá trị sử dụng khác vẫn chưa được nghiên cứu. Do đó, việc điều tra, đánh giá thực trạng đa dạng hệ thực vật hiện có ở đảo Lại Sơn là rất cần thiết, từ đó có thể cung cấp cho người dân địa phương những tri thức hữu ích về việc nhận diện, khai thác sử dụng và bảo tồn có hiệu quả hơn nguồn tài nguyên thực vật trên đảo.…”
Section: Giới Thiệuunclassified